Changes in land use and management by farm type and the impact on soil cover in Canada, 1991–2011. (September 2020) - Liu, Jiangui; Huffman, Ted; Green, Melodie; Joosse, Pamela; Martin, Tim
Highlights: A farm typological system was proposed for soil cover assessment in Canada. Farms in Canada are categorized into eight broad enterprise types. Land use and management of each farm type vary spatially and change over time. Soil cover generally increased from 1991 to 2011 for most farm types. Soil cover increased more in the prairie provinces than in eastern Canada. Abstract: A suite of indicators have been developed in Canada to assess and report on the status and trends of agri-environmental performance as impacted by agricultural production activities. The indicators include models that focus on the impact of land management practices on soil erosion, water contamination, greenhouse gas emissions, soil organic carbon and wildlife habitat. Soil Cover is one of these indicators and relates to soil protection afforded by crop canopy, crop residue and snow. It is quantified by the equivalent number of days in a year in which the soil is not exposed, and is a function of the type of crop, biomass yield, tillage, residue management practices, and weather (snow) conditions. Higher soil cover indicates a lower risk of soil erosion, better maintenance of soil organic carbon, improved wildlife habitat and lower greenhouse gas emissions. The Soil Cover Indicator has been calculated and reported on a spatial basis over the entire country every five years since 1981. Currently, the agri-environmental indicators program is being re-oriented toward assessing the environmental sustainability of different production sectors (beef, hogs, dairy, grains, oilseeds, etc.) and commodities (milk, eggs, beef, pork, etc.) rather than geographic/areal units such as soil polygons or watersheds. As an initial effort in this direction, we have developed a 'farm types' database on an ecostratification spatial framework, and have applied the Soil Cover Indicator to each farm type in order to assess its levels and changes pertaining to different farm types over the period from 1991 to 2011. The database identified land use compositions and their spatio-temporal variability typical of different types of farms. Initial outputs indicate that Beef, Other Livestock and Other Crop farm types provide the highest soil cover, Dairy and Poultry/Egg farms provide moderate levels, and Field Crop, Hog and Fruit/Vegetable farms have the lowest levels. Temporal analysis indicates a general improvement in soil cover across most farm types from 1991 to 2011.